Women and Entrepreneurship: Factors Influencing Indonesian Young Women To Be The Entrepreneur - Pratama, Dito Alif; Iswandi, Andi; I. Habibah, Inna (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2025)
This study examines the key factors that motivate young Indonesian women to engage in entrepreneurship, a field increasingly realized for its contribution to economic development and gender empowerment. In the face of ongoing unemployment and restricted access to traditional work, entrepreneurship is a feasible option, particularly for women aspiring for autonomy and economic contribution. This study investigates three primary variables—self-independence, economic status, and financial literacy—to analyze their individual and collective impacts on entrepreneurial drive among women aged 18–35 who had operated enterprises for a minimum of two years. Using a quantitative approach with multiple regression analysis, data were gathered from 107 respondents across 16 regions in Indonesia via structured questionnaires. The results show that these three factors have a big effect on young women's choices to start their own businesses, either on their own or at the same time. Self-independence, in particular, stands up as a key motivator. This shows a desire for personal freedom and a flexible work-life balance. Economic pressures and the capacity to utilize financial acumen also play a substantial role. The study adds to the field of research by giving real-world examples from Indonesia, where traditional gender roles still exist but are being challenged more and more by entrepreneurial activities. These results show how important it is to make regulations and initiatives that assist women become better entrepreneurs, learn about money, and get resources so that the economy is more open and long-lasting.